2009
DOI: 10.1016/j.ijproman.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Crossing innovation and product projects management: A comparative analysis in the automotive industry

Abstract: Projectification and platform approaches have been two main transformation trends implemented by industrial firms during the 1990s. For those firms, innovation management no longer deals with introducing radically and totally new products, but rather with applying innovative features within a regular stream of products and platforms. This paper proposes an analytical framework that can address the resulting interplay between innovative features and new products. This framework relies on the concept of innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
0
26
0
6
Order By: Relevance
“… indirecte notamment à travers les modèles d'affaires (Chanal, 2011;Chesbrough, 2010;Massa et al, 2010), la valeur pour le client (Chesbrough, 2002) ou les processus d'intéressement (Akrich et al, 1988) ou sous l'angle de la sélection et de la conduite de projet (Beaume et al, 2009), notamment dans le champ de la R&D (Cooper, 2005;Cooper, 1990), dans une perspective d'allocation et de gestion des ressources ;…”
Section: La Valeur De L'innovation Un Débat Ancien Ontologie Du Conunclassified
“… indirecte notamment à travers les modèles d'affaires (Chanal, 2011;Chesbrough, 2010;Massa et al, 2010), la valeur pour le client (Chesbrough, 2002) ou les processus d'intéressement (Akrich et al, 1988) ou sous l'angle de la sélection et de la conduite de projet (Beaume et al, 2009), notamment dans le champ de la R&D (Cooper, 2005;Cooper, 1990), dans une perspective d'allocation et de gestion des ressources ;…”
Section: La Valeur De L'innovation Un Débat Ancien Ontologie Du Conunclassified
“…A better control of the innovation process is therefore necessary and especially crucial for the integration of these innovations into vehicle projects. As stated by Beaume, Maniak, and Midler (), “innovation management no longer deals with introducing radically and totally new products, but more likely with applying innovative features within a stream of new products and platforms.”…”
Section: Innovation and Project Management In The Car Manufacturing Imentioning
confidence: 99%
“…Researchers have shown that efficient technology integration into new products is related to several characteristics: leadership capabilities and strategy (White, ); organizational structures (Lawrence & Lorsch, ; Allen, ; Iansiti, , ; Beaume et al., ); cross‐functional integration (Katz & Allen, ; Clark & Fujimoto, , ); internal communication (Allen, Lee, & Tushman, ; Roussel, Saad, & Erickson, ); decision‐making process (Beaume et al., ) and communication technologies (Allen & Hauptman, ); cooperation with suppliers (Beaume et al, ; Midler, Beaume, & Maniak, ); ‘corpus of structured knowledge’ (Freeman & Soete, ) and technological knowledge (Utterback & Abernathy, ; Von Hippel, ); as well as ‘tacit’ (Kline & Rosenberg, ), ‘sticky’ (Von Hippel, ), and ‘system knowledge’ (Henderson & Clark, ; Christensen, ; Iansiti, , ).…”
Section: Increasing the Amount And Quality Of Innovation Projects In mentioning
confidence: 99%
See 1 more Smart Citation
“…For car manufacturers, most of the time, innovations have little impact on the vehicle architecture because of their incremental nature and the fact that such innovations often concern subsystems or components [4]. A set of innovations is generally proposed by the innovation team to the team in charge of the routine design of the vehicle, which Beaume represents as an "innovative feature" flow from the innovation department to the vehicle program department, during the "contextualization phase" [5]. Both structures are completely separated (see Fig.…”
Section: Introductionmentioning
confidence: 99%